TOEFL@ CBT success - Rogers, Bruce (Peterson's/Thomson Learning, 2001)
The essential tool for mastering English proficiency tests. Each year, nearly one million international students take the English proficiency exams required for admission by US and Canadian colleges and universities. For many, TOEFL CBT Success is their number one preference for helping them achieve the high scores they'll need to earn a degree at the college of their choice. Covering all critical testing areas, it's the most in-depth instruction available. Delivering all the test-prep features for which the Peterson's Success series is rightly renowned. - "Red Alert" test-taking strategies - Key steps to improved writing ability - In depth subject review - Audio CD features listening/comprehension exercises